Pyolysin of Trueperella pyogenes Induces Pyroptosis and IL-1β Release in Murine Macrophages Through Potassium/NLRP3/Caspase-1/Gasdermin D Pathway - Liang, Hongmin; Wang, Bing; Wang, Junwei; Ma, Bo; Zhang, Wenlong (Frontiers in Immunology, 2022)
Trueperella pyogenes (T. pyogenes) is a commensal and an opportunistic pathogen of animals. This organism can cause inflammatory diseases, such as pneumonia, mastitis and endometritis in hosts. However, the molecular basis for the pro-inflammatory properties of this organism is still largely unknown. In the current study, using murine macrophages as model, the ability of T. pyogenes to induce pyroptosis was first determined. Then, pyolysin (PLO), a cholesterol-dependent cytolysin secreted by T. pyogenes, was found to be closely related to T. pyogenes-induced pyroptosis. Next, our work showed that PLO can form pores in the cell membrane, leading to the efflux of potassium (K+), NLRP3 inflammasome-mediated caspase-1 activation, and gasdermin D (GSDMD) cleavage. Inhibition of the K+/NLRP3/caspase-1/GSDMD pathway abolished T. pyogenes and PLO-induced IL-1β release. Taken together, these results indicate T. pyogenes-induced inflammation is related to PLO-induced pyroptosis and IL-1β release. Our work shed light on the pathogenesis of T. pyogenes and the interaction between T. pyogenes and hosts’ immune system.